Thermogravimetric analysis of microplastics: A mini review - Rola Mansa; Shan Zou (Environmental Advances, 2021)
This mini review identifies several thermogravimetric analysis (TGA)-based methods for the identification and quantification of different microplastics in both proof-of-concept studies and environmental samples, and highlights method-specific limitations associated with their application. Well-separated and non-overlapping melting peaks are a conditional requirement for the identification and quantification of microplastics using thermogravimetric analysis-differential scanning calorimetry (TGA-DSC). Other TGA-based methods, such as coupled Fourier transform infrared spectroscopy (TGA-FTIR) or mass spectrometry (TGA-MS), as well as thermal extraction desorption-gas chromatography-mass spectrometry (TED-GC-MS), are dependent on the presence of at least one unique thermal degradation product for use as a marker in the identification and quantification process. Varying degrees of time expenditure and complexity of analysis are present within the reviewed methods, with one consistent factor underlying the evaluation: an underutilization of information extracted from the TGA signal itself. As such, in this mini-review, we advocate the development of methods in which stand-alone TGA can be applied towards the chemical identification of microplastics. Although the main hindrance to this is the presence of overlapping thermal transitions, stand-alone TGA has long been used as a routine and robust method for the analysis of polymers, and methods for optimizing the resolution of complex mixtures are available. Current results in literature emphasize the complementarity of analysis methods, and TGA has potential to play a role as a rapid and facile method that can guide the chemical identification of polymers and address needs of current methods.